2010
DOI: 10.1002/ajp.20726
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating for long‐term impact of an environmental education program at the Kalinzu Forest Reserve, Uganda

Abstract: Although the importance of evaluating the effectiveness of conservation education programs cannot be underestimated, few evaluations of these programs and their resulting impact on the environment have been conducted. A partnership between scientists, educators, and local administrators on an evaluation program has been developed to evaluate a model of education program evaluation that includes short- and long-term evaluation of (1) knowledge and attitude change, (2) behavior change, and (3) positive biologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
72
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 114 publications
(92 citation statements)
references
References 13 publications
3
72
0
3
Order By: Relevance
“…It should be noted that in the aforementioned categories, learning outcomes of the group using the additional materials were clearly better than those of students using only the comic book so peer-to-peer learning in smaller groups had a positive effect not only on overall knowledge acquisition, but also on the acquisition of more complex, interconnected and abstract forms of knowledge. The study, therefore, adds to the so-far-small body of empirical evaluation studies carried out under the challenging conditions of developing countries compared to evaluation studies in Western countries [50,52,55,66,68]. Providing environmental education for students proves to have a measurable and lasting positive effects [85].…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…It should be noted that in the aforementioned categories, learning outcomes of the group using the additional materials were clearly better than those of students using only the comic book so peer-to-peer learning in smaller groups had a positive effect not only on overall knowledge acquisition, but also on the acquisition of more complex, interconnected and abstract forms of knowledge. The study, therefore, adds to the so-far-small body of empirical evaluation studies carried out under the challenging conditions of developing countries compared to evaluation studies in Western countries [50,52,55,66,68]. Providing environmental education for students proves to have a measurable and lasting positive effects [85].…”
Section: Discussionmentioning
confidence: 94%
“…Kuhar et al [68] also found evidence for long-term knowledge retention of their environmental education program in Uganda. They observed some trends towards a continued performance increase over time they attributed to follow-up instructions in class, older students transferring knowledge to siblings, friends and family and a sort of institutional learning of schools and teachers that were involved in EE programs for many years.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations